Monitoring Galvanic Replacement Through Three-Dimensional Morphological and Chemical Mapping - Goris, Bart; Polavarapu, Lakshminarayana; Bals, Sara; Van Tendeloo, Gustaaf; Liz-Marzán, Luis M (Nano letters, 2014)
Galvanic replacement reactions on metal nanoparticles are often used for the preparation of hollow nanostructures with tunable porosity and chemical composition, leading to tailored optical and catalytic properties. However, the precise interplay between the three-dimensional (3D) morphology and chemical composition of nanostructures during galvanic replacement is not always well understood as the 3D chemical imaging of nanoscale materials is still challenging. It is especially far from straightforward to obtain detailed information from the inside of hollow nanostructures using electron microscopy techniques such as SEM or TEM. We demonstrate here that a combination of state-of-the-art EDX mapping with electron tomography results in the unambiguous determination of both morphology transformation and elemental composition of nanostructures in 3D, during galvanic replacement of Ag nanocubes. This work provides direct and unambiguous experimental evidence toward understanding the galvanic replacement reaction. In addition, the powerful approach presented here can be applied to a wide range of nanoscale transformation processes, which will undoubtedly guide the development of novel nanostructures.